Long-Term Mortality and Functional Outcomes After Extracorporeal Membrane Oxygenation in Critically Ill Adults: A Systematic Review and Meta-Analysis - Kaylee T. Stebbins; Chun Yee Yap; Lois Segun-Beloved; Alexandra M. Hodgson; Anais Charles-Nelson; Ary Serpa Neto; Jayatee Banerjee; Lane Meredith; Lorena Romero; Vicki Papanikolaou; Zhomart Orman; Carol L. Hodgson; et al. (Critical Care Medicine, 2026)
Objectives: To evaluate long-term all-cause mortality and functional outcomes among critically ill adults treated with extracorporeal membrane oxygenation (ECMO), including differences by ECMO modality and clinical indication. Data Sources: Ovid MEDLINE, Embase, Emcare, Central Register of Controlled Trials, and Scopus were searched to March 2025. Study Selection: Randomized controlled trials and observational studies reporting mortality or functional outcomes at or beyond 6 months in adults receiving ECMO were eligible for inclusion. Data Extraction: A systematic review and meta-analysis were conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines and prospectively registered with PROSPERO (CRD420251002639). Two reviewers independently extracted data. Mortality was pooled using random-effects meta-analysis with 95% CIs. Prespecified subgroup analyses examined ECMO modality and clinical indication. Sensitivity analyses assessed the impact of missing outcome data. Functional outcomes were narratively synthesized due to heterogeneity. Data Synthesis: A total of 163 studies including 78,053 adults met inclusion criteria, with 59,454 adults in 156 of 163 studies (95.7%) contributing to mortality meta-analyses. At 1 year, pooled mortality was 37.2% (95% CI, 30.0–45.1%) in 13 of 33 venovenous ECMO studies (39.4%), 55.2% (95% CI, 50.2–60.1%) in 42 of 55 venoarterial ECMO studies (76.4%), and 74.4% (95% CI, 71.4–77.2%) in 14 of 24 (58.3%) extracorporeal cardiopulmonary resuscitation (ECPR) studies. Functional outcomes were reported in 38 of 163 studies (23.3%) in 7,876 survivors and were assessed using various instruments, most commonly the Cerebral Performance Category in 20 of 38 studies (52.6%), the World Health Organization Disability Assessment Schedule 2.0 in five of 38 studies (13.2%), and the modified Rankin Scale in five of 38 studies (13.2%). Conclusions: Long-term mortality following ECMO differed substantially by ECMO modality, ranging from 37.2% among adults receiving venovenous ECMO to 74.4% among adults receiving ECPR. Functional outcomes were inconsistently reported, limiting the understanding of functional recovery among survivors. Standardized reporting and benchmarking are required to better inform long-term prognosis, patient selection, and factors that may improve functional recovery after ECMO.